Analisis Biaya dan Willingness to Pay Pengelolaan Limbah dengan IPAL Komunal di Sentra Industri Penyamakan Kulit Sukaregang: Cost and Willingness to Pay Analysis for Waste Management Using Communal Wastewater Treatment Plants in Sukaregang Leather Tanning Industry - Amelia, Tiara Putri; Amanda, Dea; Sehabudin, Ujang (IPB University, 2025)
Tanned leather is one of the flagship products of Garut Regency, with a centralized cluster of craftsmen located in the Sukaregang leather tanning industry. The tanning process generates waste that must be treated before being discharged into the environment. The government has built three communal wastewater treatment plants (WWTPs) that function as treatment facilities for the industrial waste produced by the leather tanning sector. However, currently, all communal WWTPs are not operating due to various constraints, one of which is related to operational and maintenance budget. This study aims to: (1) analyze the perceptions of business actors regarding the provision of communal WWTPs; (2) estimate the operational and maintenance costs of communal WWTP; and (3) analyze the value of willingness to pay (WTP) and factors influencing business actors’ probability to contribute to waste management with communal WWTPs. The methods used include cost analysis, descriptive analysis using a Likert scale, Contingent Valuation Method, and logistic regression analysis. The results of the study indicate that: (1) business actors stated that they agree with the perceptions related to social, economic, and environmental aspects, but strongly disagree with the technical aspects; (2) the estimated operational and maintenance costs for the three communal WWTPs in Sukaregang with a capacity of 1.300m3/day amount to IDR 57.696.630/month, with a wastewater treatment cost of IDR 1.500/m3; (3) the total WTP estimation reaches IDR 63.868.038,86/month with an average WTP value of IDR 2.801,23/m3, and the factors that significantly influence the WTP are the bid value, income, and length of business operation. Kulit samak merupakan salah satu produk unggulan Kabupaten Garut, dengan sentra pengrajin terpusat di industri penyamakan kulit Sukaregang. Proses penyamakan kulit menghasilkan limbah yang harus diolah terlebih dahulu sebelum dibuang ke lingkungan. Pemerintah membangun tiga IPAL Komunal yang berfungsi sebagai tempat pengolahan limbah industri penyamakan kulit. Namun, pada saat ini seluruh IPAL Komunal tidak beroperasi karena mengalami berbagai kendala salah satunya terkait anggaran operasional serta pemeliharaan. Penelitian ini bertujuan untuk: (1) menganalisis persepsi pelaku usaha terkait penyediaan IPAL Komunal; (2) mengestimasi biaya operasional serta pemeliharaan IPAL Komunal; dan (3) menganalisis besar WTP serta peluang faktor-faktor yang mempengaruhi peluang pelaku usaha untuk berkontribusi dalam pengelolaan limbah dengan IPAL Komunal. Metode yang digunakan yaitu, analisis deskriptif menggunakan Skala Likert, analisis biaya, Contingent Valuation Method, dan analisis regresi logistik. Hasil penelitian menunjukkan bahwa: (1) pelaku usaha menyatakan setuju terhadap persepsi yang berkaitan dengan aspek sosial, ekonomi, dan lingkungan, namun menyatakan sangat tidak setuju pada aspek teknis khususnya terkait regulasi penggunaan IPAL Komunal; (2) estimasi biaya operasional dan pemeliharaan untuk ketiga IPAL Komunal di Sukaregang dengan kapasitas 1.300m3/hari adalah sebesar Rp57.696.630/bulan, dengan biaya pengolahan air limbah Rp1.500/m3; (3) estimasi total WTP pelaku usaha mencapai Rp63.868.038,86/bulan dengan nilai rataan WTP sebesar Rp2.801,23/m3, serta faktor-faktor yang berpengaruh signifikan terhadap kesediaan pelaku usaha untuk berkontribusi dalam pengelolaan limbah adalah nilai penawaran (bid), pendapatan, dan lama usaha.